Data underlying the publication: Pathways and watermass transformation along and across the Mohn-Knipovich Ridge in the Nordic Seas - Ypma, Stefanie (4TU.Centre for Research Data, 2020)
Mean fields and lagrangian particle data set used for publication in JGR.